Principles of Entrepreneurship (ENT530): Business Model Canvas: The Happy Bakers / Surawati Rahimin ... [et al.] - Rahimin, Surawati; Mohd Zamri, Siti Nur Fatihah; Mat Zaid, Nurul Faraheen; Alias, Muhammad Asnawi Izuan; Bidin, Akmal Hafiz (2020)
At this time the bakery business is gaining popularity from customers. This business is also growing in Malaysia. The Happy Bakers located at Taman Lagenda Melaka .We specialize in the production of buns, pastries, cakes and cookies. The Happy Bakers is a business that carries out activities of making, accepting orders and also distributing bakery-based products such as various types of cakes such as cupcakes, macaroon, cookies and various types of cakes. We also accept online booking, phone and even walk in. The Happy Bakers is located in the center of Melaka which is the focus of many, including tourists from outside Melaka. We chose this place because of the dense population distribution and close to big supermarkets like Aeon and Tesco. We provide services to make and sell cakes, breads, cookies, buns and pastries to residents around the city of Melaka. We accept orders for various occasions such as ordering ‘cupcakes’ as souvenirs for certain occasions. We have distributed many 'brochures' in residential areas and offices to get information about our business. In fact, we have also built a website for customers to see examples of these bakeries in more detail. Therefore, customers can make a reservation through the website provided or contact us by phone number on the ‘brochure’ appendix and has been distributed at any convenient time. All negotiations will be conducted well according to customer's request.